Pure Formalities: Living With the Nescient Dead, or the Dead Who Don't Know They Are Dead. - Hardack, Richard (Contemporary Literature)
In the article, the author analyzes the contemporary writing genre about nescient dead (ND) or the dead people who do not know they are already dead. Other topics include the periodization and historicity questions raised by ND on such issues as genre, knowledge, technology, and diaspora, as well as cultural patrimony and some literary examples like "The Sixth Sense,""Ubik," and "White Noise."